2021
DOI: 10.1002/ange.202108207
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Protected Au55 with a Novel Structure and Remarkable CO2 Electroreduction Performance

Abstract: A Au55 nanocluster with the composition of [Au55(p‐MBT)24(Ph3P)6](SbF6)3 (p‐MBT=4‐methylbenzenethiolate) is synthesized via direct reduction of gold‐phosphine and gold‐thiolate precursors. Single‐crystal X‐ray diffraction reveals that this Au55 nanocluster features a face‐centered cubic (fcc) Au55 kernel, different from the well‐known two‐shell cuboctahedral arrangement in Au55(Ph3P)12Cl6. The Au55 cluster shows a wide optical absorption band with optical energy gap (Eg=1.28 eV). It is found that the exclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…The critical role halide plays in nanocluster synthesis was reported by Wang et al., who prepared the phosphine/thiolate-stabilized Au nanocluster, [Au 55 (PPh 3 ) 6 ( p -MBT) 24 ] 3+ ( p -MBT = 4-methylbenzene thiolate), by coreduction of Ph 3 PAu­(SbF 6 ) and p -MBTAu in a “halide-free” environment . In the presence of halide under otherwise identical reduction conditions, the previously known [Au 25 ( p -MBT) 5 (Ph 3 P) 10 Cl 2 ] 2+ cluster was obtained …”
Section: Resultsmentioning
confidence: 99%
“…The critical role halide plays in nanocluster synthesis was reported by Wang et al., who prepared the phosphine/thiolate-stabilized Au nanocluster, [Au 55 (PPh 3 ) 6 ( p -MBT) 24 ] 3+ ( p -MBT = 4-methylbenzene thiolate), by coreduction of Ph 3 PAu­(SbF 6 ) and p -MBTAu in a “halide-free” environment . In the presence of halide under otherwise identical reduction conditions, the previously known [Au 25 ( p -MBT) 5 (Ph 3 P) 10 Cl 2 ] 2+ cluster was obtained …”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the origin of the active sites of these Au clusters for CO 2 reduction remains fairly controversial, owing to the identification of the active sites based on the DFT calculations rather than the experimental evidence. Besides, several Au n clusters with novel structures have been also reported to show superior electrochemical activity for CO 2 conversion to the gold nanoparticles with large size. …”
Section: Electrochemical Reduction Of Co2 Over Au-based Clustersmentioning
confidence: 99%
“…We found that the [Au 22 H 3 ] 3+ cluster shows higher FE toward CO than the [Au 11 ] 3+ cluster under all voltages. When more negative potentials are applied, the FE first increases and then decreases, reaching a maximum at about −0.6 V. This trend is similar to the recently reported phosphine/thiolate coprotected Au 55 cluster . The best catalytic performance of [Au 22 H 3 ] 3+ was observed at −0.6 V with an FE CO of 92.7%, which is significantly higher than that of the thiolate-protected Au 25 cluster at a similar potential .…”
mentioning
confidence: 91%